Integrating AI-based paraphrasing into academic writing pedagogy: A reflective study on Quillbot in practice - Herda, Rozanah Katrina; Margana, Margana; Sain, Zohaib Hassan; Savitskaya, Elina S.; Santiana, Santiana; Principe, Regine Aguilar (TLEMC (Teaching and Learning English in Multicultural Contexts), 2025)
Integrating artificial intelligence (AI) into education has transformed traditional approaches to teaching and learning, particularly in academic writing instruction. This study investigates the pedagogical impact of using QuillBot, an AI-based paraphrasing tool, on students' academic writing performance and their perceptions of its use. Motivated by the increasing complexity of academic writing and the need for instructional innovation, this mixed-methods research examines learning outcomes and student experiences. Forty-fourth-semester students, consisting of 13 male and 27 female students, enrolled in an Academic Writing course, participated in the study. An explanatory sequential design was employed, starting with pre- and post-tests measuring writing performance, followed by semi-structured interviews to explore students' reflections. The results revealed a significant improvement in students' writing scores, with the mean increasing from 49.25 (pre-test) to 74.00 (post-test), indicating enhanced ability in paraphrasing and producing coherent academic texts. Students also reported that QuillBot helped them internalize academic language structures, improved their awareness of sentence patterns, and supported autonomous learning by providing immediate, accessible feedback. Moreover, they acknowledged the importance of ethical usage and viewed the tool as a guide rather than a shortcut. These insights highlight the dual role of AI tools as both linguistic support systems and pedagogical aids when thoughtfully integrated into instruction. Future research should consider broader and more diverse populations to deepen understanding of how AI-assisted writing tools shape student learning across different educational contexts.Keywords: Academic writing, Paraphrasing, Artificial intelligence, Quillbot